Characteristic of Electric Field for XLPE Under Normal and Moisture Condition Using COMSOL Multiphysics - Spawie, Fikry Hariez; Mohd Jamail, Nor Akmal; Kamarudin, Qamarul Ezani (Journal of Electronic Voltage and Application, 2024)
Cross-linked polyethylene cables (XLPE cables) have gained significant popularity in transmission lines for urban pipeline corridors due to their exceptional electrical and mechanical properties. However, prolonged usage of XLPE cables can result in degradation and eventual disintegration. This research aims to investigate the characteristics of XLPE under normal and moisture absorption conditions to address the prevalent insulation and corrosion faults observed in Malaysia, particularly during the annual flooding caused by the northeast monsoon. An experiment is conducted on an 11 kV XLPE-insulated underground cable to examine the changes in XLPE’s conditions and the intensity of its electric field. Four moisture conditions are examined, including virgin XLPE, XLPE effect of distilled water absorption, XLPE with effect of distilled water and peat soil, and XLPE with effect of distilled water and clay. The relative permittivity of each sample is measured using the Keysight 16451B dielectric test fixture, and an electrostatic model of XLPE is developed using COMSOL Multiphysics for analyzing the electric field properties. Comparative simulation results reveal varying electric field intensities for each sample, with Sample 1 (virgin XLPE) exhibiting maximum and minimum electric field intensities of 10.0718 MV/m and 4.2380 MV/m, respectively, and Sample 4 (XLPE with effect of distilled water and clay) displaying maximum and minimum intensities of 10.0920 MV/m and 4.2353 MV/m, respectively. These findings contribute to a better understanding of XLPE’s performance in moisture-rich environments and facilitate the development of more robust insulation materials for electrical applications.